Delamination failure of composite containment vessels subjected to internal blast loading. (15th October 2015) - Zheng, Jinyang; Hu, Yang; Ma, Li; Du, Yang
Abstract: Delamination failure of composite vessels subjected to internal blast loading was studied in this paper. Experiments were conducted on several e-glass/epoxy vessels with aluminum lining. Micro observation and fracture analysis indicated that delamination failure occurred under a wide range of explosive loadings. A finite element model was also established to explore the delamination initiation mechanism and the evolution of dynamic behavior. Delamination simulation was achieved using a tiebreak contact model and a cohesive criterion. Numerical results from the finite element analysis were compared with experimental data, which indicated that both dynamic response and delamination failure are in good agreement. An analysis of dynamic response highlighted the amplitude and phase inconsistency between neighbor layers during the vibration process, which is considered the main cause of delamination failure. The dynamic behavior evolution of delamination under different explosive loading conditions was investigated by setting a small pre-delamination in the numerical model. Results showed that the pre-delamination ignited continuous delamination in different scales of length. With the increment of explosive charge, pre-delamination extended more rapidly with many new delamination appearing and several delamination fusing with the bigger one during the extension.